Second Grade Spanish Reading. Teacher's Manual - Bay Area Bilingual Education League, Berkeley, CA.; Bay Area Bilingual Education League, Berkeley, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This is a Spanish reading guide for the bilingual Spanish-English second grade teacher. The guide contains twenty-eight objectives to be mastered, with the corresponding tests. The emphasis is on encoding, decoding, vocabulary, and comprehension. (CFM)
Availability: Bay Area Bilingual Education League, 1414 Walnut Street, Berkeley, California 94709.
Educational level discussed: Primary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingual Education; Decoding (Reading); Educational Objectives; Instructional Materials; Language Instruction; Language Tests; Primary Education; Reading Comprehension; Reading Development; Reading Instruction; Reading Tests; Second Language Learning; Spanish; Teaching Guides; Vocabulary; Guides, General